The Differences Cost of Equity Capital between Before and After Adoption of IFRS - Sanjaya, I Putu Sugiartha; Br. Barus, May Hosiani (Jurnal Keuangan dan Perbankan, 2017)
The objective of this study was to analyze and compare between the cost of equity capital between before and after the adoption of IFRS on Statement of Financial Accounting Standard Financial Instrument (PSAK) for banking companies listed in Indonesian Stock Exchange. The period on this study was 2008-2009 for before adoption and 2013-2014 for after adoption. Data on this study was secondary data such as annual financial reporting and share price. Cost of equity capital was measured using the Ohlson Model. The sample in this study was banking companies listed in Indonesian Stock Exchange in 2008, 2009, 2013, and 2014. Selecting a sample was by purposive sampling with specific criteria. Results of this study proved that the cost of equity capital was lower for after adoption of IFRS on Statement of Financial Accounting Standard Financial Instrument for banking companies listed in Indonesian Stock Exchange than before adoption. It meant that adoption IFRS could reduce the cost of equity capital. This result had an impact on reducing the non-performing loan, increasing the loan to deposit ratio, and increasing net interest margin.DOI: https://doi.org/10.26905/jkdp.v21i4.1479